Material failure of an AISI 316L stainless steel hip prosthesis - Godec, Matjaž (Materiali in tehnologije, 2011)
One of the major successes of modern surgery is the total replacement of joints by timplantation of prosthetic components by which the pain is relieved and deformity is corrected. The aseptic loosening of a prosthetic-joint component is the most common reason for joint-revision surgery. Furthemore, it is thought that wear particles are one of the major contributors to the development and perpetuation of aseptic loosening. It was ascertained that besides wear particles originated from polyethylene acetabular cup, the main reason of loosening hip prosthesis was due to the material failure. Based on stem material examination by different techniques it was found out that improper microstructure caused additional abrasion by hard particles and aseptic loosening took place.
Keywords: proteze; materiali; obraba; nerjavno jeklo; polietilen; nekovinski vključki